142 Heat stress affects piglet productivity and well-being during pre- and postnatal development. (7th December 2018) - Johnson, J
Abstract: Heat stress (HS) negatively impacts piglet productivity and well-being as animals attempt to manage the resultant strain response. This is especially true when HS is combined with production stressors (e.g. mixing, weaning, transport, handling, and isolation) that have the potential to increase disease occurrence, morbidity and mortality. While pigs can utilize adaptive physiological mechanisms to compensate these are often unfavorable to efficient livestock production. Specifically, HS decreases weight gain, reduces growth and production efficiency, alters carcass composition, and results in greater morbidity and mortality. As a result, decreased animal performance can cause profit losses for producers and affect economic sustainability. In addition to the negative effects of postnatal HS, prenatal HS may have long-term consequences that may compromise future piglet well-being and performance. Pigs gestated in HS conditions may have a greater postnatal stress response and an increase in maintenance energy requirements. Furthermore, prenatal HS decreases piglet birth weight, and increases teratogenicity, core body temperature set-point, and alters postnatal body composition during postnatal life potentially leading to long-term production losses. Taken together, the effects of HS during pre- and postnatal development compromises productivity and well-being of piglets thereby threatening the sustainability of global animal agriculture.